Iron supplementation: Oral tablets versus intramuscular injection - Dawson, B.; Goodman, C.; Blee, T.; Claydon, G.; Peeling, P.; Beilby, J.; Prins, A. (International Journal of Sport Nutrition and Exercise Metabolism, 2006)
Non-anemic, iron depleted women were randomly assigned to an injection group (IG) or oral group (OG) to assess which method is more efficient for increasing iron stores over a short time period. IG received a course of 5 × 2 mL intramuscular injections over 10 d, and OG received one tablet daily for 30 d. Fourteen, 21 and 28 d after commencing supplementation, ferritin concentration in OG significantly increased from baseline (means ± standard error: 27 ± 3 to 40 ± 5 to 41 ± 5 to 41 ± 5 mg/L; P < 0.01). Similarly, on days 15, 20, and 28 post the first injection, ferritin concentration in IG significantly increased from baseline (means ± standard error: 20 ± 2 to 71 ± 17 to 63 ± 11 to 63 ± 7 mg/L; P < 0.01), and was also significantly greater than OG at day 15 and 28 (P < 0.05). Iron injections are significantly more effective (both in time and degree of increase) in improving ferritin levels over 30 d than oral tablets.